Research of the factors influencing the operational performance of urban public transport - Skirkouski, S.; Sedziukevich, U.; Karpenko, V.; Svichynskyi, S.; Скірковський, С. В.; Седюкевич, В. М.; Карпенко, В. О.; Свічинський, С. В. (Харківський національний автомобільно-дорожній університет, 2021)
Problem. Currently, there is no universal approach to improve the efficiency of the urban public transport operation. Different methods are used during the estimation of public transport operation cost and the quality of services for the passengers. It makes actual the development of the target function which will allow assessing the carrier cost and passenger expenditures, and therefore find the balance between the interests of these parties of the transportation process. Thus, the alternative to the existing approaches can be created and then used to organize passenger transportation and improve transport enterprise management. Development of this alternative is the actual task as the new target function will open the horizon to improve the methods of organization of public transport operation. Goal. The new approach to optimize the costs of public transport operation needs to be tested for the appropriateness for the planning of passenger service in cities. Methodology. The developed target function was derived as the result of the analysis of the economic and social factors influencing the efficiency of the urban public transport operation. Results. The use of the developed target function allows finding the optimal values of cost components for the passenger and the carrier. Originality. The obtained function to optimize the performance of public transport allows reducing the costs of suboptimal use of vehicles capacity, suboptimal allocation of the vehicles to the routes and the irrational organization of vehicles operating on the routes. Practical value. The results of the research clarify the controlled and uncontrolled parameters of the public transport system operation.
Дослідження факторів, що впливають на ефективність роботи міського громадського транспорту
Keywords: passenger transportation; public transport; optimal capacity; headway; waiting time; пасажирські перевезення; громадський транспорт; оптимальна пасажиромісткість; інтервал руху; час очікування; 656.072; 10.30977/AT.2219-8342.2021.48.0.45